2005
DOI: 10.1159/000087557
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine Oxidase Activity and Tri-Iodothyronine Level in Violent Offenders with Early Behavioural Problems

Abstract: The focus is on evaluating the relationships between early behavioural problems and biochemical variables at adult age and their significance for early criminality and violent behaviour in a life perspective. In the present study, using prospective longitudinal data, a sample of males with a history of early criminal behaviour and male controls (n = 103) were investigated concerning (1) teacher-rated behaviours at age 11–14 years; (2) platelet monoamine oxidase (MAO) activity and tri-iodothyronine (T3 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…A study conducted by Eklund et al evaluated the relationship between behavioural disorders at early ages and biochemical variables in adulthood and their importance in terms of early crime and lifetime violent behaviours. e results showed a significant combined risk level pattern of low MAO activity and high T3 level in violent offenders with early behavioural risk patterns [15].…”
Section: Introductionmentioning
confidence: 82%
“…A study conducted by Eklund et al evaluated the relationship between behavioural disorders at early ages and biochemical variables in adulthood and their importance in terms of early crime and lifetime violent behaviours. e results showed a significant combined risk level pattern of low MAO activity and high T3 level in violent offenders with early behavioural risk patterns [15].…”
Section: Introductionmentioning
confidence: 82%
“…Models effective in group differentiation are likely to generalize to independent datasets and are characterized by high CVC and accuracy, specificity, and sensitivity greater than .5. MDR is a relatively new approach, and the software, although it has been successfully applied [Andrew et al, 2006;Coutinho et al, 2007;Huang et al, 2007;Li et al, 2008;Ni et al, 2009;Park et al, 2007], has not yet penetrated the psychological literature, although there have been analogous attempts to consider multiple configurations of various risk, even if not genetic, factors for theory [Magnusson, 1999], for methodology [Lienert et al, 1990], and for illustration [Eklund et al, 2005]. The issue of multiple comparisons was handled differently for the different types of analyses (see below).…”
Section: Analytic Planmentioning
confidence: 99%
“…Eklund et al [6] found that low MAO activity and high tri-iodothyronine (T3) level were significantly associated with violent offenders with an early behavioural risk pattern. They further reported that attention difficulties were associated with low MAO activity.…”
Section: Introductionmentioning
confidence: 99%